Simulation Study of Effects, Operating Temperature and Layer Thickness on Thin Film CIGS Solar Cell Performance - A.D. Pogrebnjak; A.K.M. Muhammed (Журнал нано- та електронної фізики)
SCAPS- program is designed basically for the simulation and studying the properties of photonic devices. We explored the important controllable design parameters affecting the performance of the hetero junction solar cells, as operating temperature that we noticed increasing in J-V characteristics by increasing T, the effect of thickness of each layer on the performance of the cell was studied, an increasing of J-V characteristics with increasing p-layer , In the numerical example, 3 μm absorber layer and CdS layer 0.05 μm, ZnO layer 0.1 μm, works the best for given doping density, if we change the optimum value , the efficiency can reach to 17.72 % with FF 83.88 %, Voc = 0.725 Volt, Jsc = 29.07 mA/cm2 at 300 K, in this case, we have come out the optimum parameters to achieve the best performance of this type of cell, and then to made comparison with practical CIGS cell.